2019
DOI: 10.3390/biom9060241
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes of β and HPβ-Cyclodextrin with α, β Amyrin and In Vitro Anti-Inflammatory Activity

Abstract: α, β amyrin (ABAM) is a natural mixture of pentacyclic triterpenes that has a wide range of biological activities. ABAM is isolated from the species of the Burseraceae family, in which the species Protium is commonly found in the Amazon region of Brazil. The aim of this work was to develop inclusion complexes (ICs) of ABAM and β-cyclodextrin (βCD) and hydroxypropyl-β-cyclodextrin (HPβCD) by physical mixing (PM) and kneading (KN) methods. Interactions between ABAM and the CD’s as well as the formation of ICs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Due to the progress of nanomaterials, the assessment of the biological activity of precursor compounds for OA and UA, i.e., α- and β- amyrines, could also be considered. Earlier research results indicated the possibility of introducing amyrins into nano emulsions [ 89 ] or β-cyclodextrins [ 90 ]. Their possible anticancer activity should be evaluated in novel nanoformulations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the progress of nanomaterials, the assessment of the biological activity of precursor compounds for OA and UA, i.e., α- and β- amyrines, could also be considered. Earlier research results indicated the possibility of introducing amyrins into nano emulsions [ 89 ] or β-cyclodextrins [ 90 ]. Their possible anticancer activity should be evaluated in novel nanoformulations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite indicating good intestinal absorption, high log P values indicate low water solubility, which can lead to low oral bioavailability. The pharmacokinetics of compounds 8 , 15 and 17 have already been studied and their oral bioavailability can be improved by formulations such as nanoemulsions, nanoparticles, liposomes, polymeric micelles and cyclodextrin complexes (Abriata et al, 2017; Cavazos‐Garduño et al, 2015; Da Silva Júnior et al, 2019; Kumar et al, 2018; Liu et al, 2016; Moura et al, 2020; Qiu et al, 2019; Rodrigues et al, 2013; Soica et al, 2014; Wang et al, 2019; Zhou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…With γ CD, a significant reduction in the main ABAME reflection was also observed, in addition to secondary reflections distinct from those of the individual components; this occurred mainly with the IC prepared with γ CD at the 2:1 molar ratio by rotary evaporation (EVG2), which showed medium-to-low intensity reflections at 7°, 14°, 15°, and 16° different from the other systems. These results suggest that the three proposed systems have a crystalline phase distinct from the isolated components, which is, therefore, an indication of complexation [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%